Model Kolaborasi Hexahelix dalam Peningkatan Kesetaraan Gender di Kampung Keluarga Berkualitas Kota Banjar - Purnama, Riza; Girsang, Nova Chalimah; Nurjanah, Dara Siti (Universitas Islam Lamongan, 2025)
This community service activity was motivated by the high divorce rate and low family participation in family resilience programs in Banjar City, particularly in Kampung KB Rampak Polah. The program aims to increase community awareness and understanding of gender equality issues through the collaborative Hexahelix model approach. The implementation method involves participatory training by engaging six key actors: academics, government, business, media, communities, and law enforcement. This activity successfully formed the HCG (Hexahelix Collaboration for Gender) group and increased women's involvement in decision-making at the community level. These results indicate that a cross-sector collaborative approach is effective in promoting sustainable gender equality.